Myth, Memory and Misunderstanding: Irish-Australian Identity in Peter Carey's 'True History of the Kelly Gang' - Marija Pericic (Limina: A Journal of Historical and Cultural Studies, 2009)
In this text, Peter Carey creates a Ned Kelly at a far remove from the traditional heroic image of the outlaw. Carey's Kelly is a complex and problematical figure of struggling Irish-Australian identity, and the text explores the cultural dialogue between Ireland and Australia and the way that it has shaped both personal and national identity construction. Memory, both individual and collective, is central to the construction of these identities, along with the fabrication, misunderstanding, nostalgia and selectiveness that form a part of the process of remembering. As Carey draws attention to the constructed nature of Kelly's identity and challenges the reliability and political implications of Kelly's Irish cultural memory, he simultaneously questions Australia's cultural memory of the Ned Kelly story.